Existence of a solution to the problem posed for a system of fractional diffusion equations: Existence of a solution to the problem posed for a system of fractional diffusion equations - Turdiev, Khalim; Bahronova, Sayyora; Amrulloyeva, Zarina (MODERN PROBLEMS AND PROSPECTS OF APPLIED MATHEMATICS, 2024)
In recent years the field of fractional calculus has attracted interest of researchers in several areas including mathematics, physics, chemistry, engineering and even finance and social sciences. The initial, initial boundary value problem for frac